2017
DOI: 10.1007/s10734-017-0204-3
|View full text |Cite
|
Sign up to set email alerts
|

Administrators in higher education: organizational expansion in a transforming institution

Abstract: Recent European research has revealed growth in the number of administrators and professionals across different sections of universities-a long established trend in US universities. We build on this research by investigating the factors associated with variation in the proportion of administrators across 761 Higher Education Institutions (HEIs) in 11 European countries. We argue that the enactment of expanded and diversified missions of HE is one of the main factors nurturing universities' profesional and admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 42 publications
(46 reference statements)
2
50
0
3
Order By: Relevance
“…This is largely related to the slow changes in the public perceptions about the merit of individual HEIs (Keith 2001), whereby reputation feeds into research funding and research networks, shapes employers' perceptions of graduate employability and influences students' choice of university. The findings are equally relevant for the wider neo-institutional literature documenting the diffusion of organisation as a model of institutional identity and purpose (Meyer 2000;Meyer and Bromley 2013;Baltaru and Soysal 2017). In this sense, universities are increasingly behaving as strategic actors, despite there being little evidence for the capacity of individual institutions to produce outputs via purposive organisational action.…”
Section: Reputation Vs Organisationmentioning
confidence: 75%
See 1 more Smart Citation
“…This is largely related to the slow changes in the public perceptions about the merit of individual HEIs (Keith 2001), whereby reputation feeds into research funding and research networks, shapes employers' perceptions of graduate employability and influences students' choice of university. The findings are equally relevant for the wider neo-institutional literature documenting the diffusion of organisation as a model of institutional identity and purpose (Meyer 2000;Meyer and Bromley 2013;Baltaru and Soysal 2017). In this sense, universities are increasingly behaving as strategic actors, despite there being little evidence for the capacity of individual institutions to produce outputs via purposive organisational action.…”
Section: Reputation Vs Organisationmentioning
confidence: 75%
“…The proliferation of non-academic professionals is argued to be symptomatic of the university increasingly articulating its identity as a purposive organisational actor i.e. 'an integrated, goal-oriented entity that is deliberately choosing its own actions and that can thus be held responsible for what it does' (Krücken 2011, 4, see also Baltaru and Soysal 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Universities are expected to employ more professional staff in strategic areas such as student recruitment (Lynch 2006) and to expand their human resources in order to deal with the operational needs associated with a larger student body (Gibb et al 2012). However, recent European-level research has shown that the relationship between administrative staff and the overall increase in student numbers is overestimated (Baltaru and Soysal 2017). The alternative perspective puts forward the argument that the proliferation of non-academic professionals can be best understood against the backdrop of new goals and missions assimilated by universities (Krücken 2011) that foster the growing differentiation of functions at the organisational level (Schneijderberg and Merkator 2013).…”
Section: Universities' Higher Education Professionalsmentioning
confidence: 99%
“…Recent research, on the other hand, shows that universities indeed adopt similar organisational responses by expanding and diversifying the body of their professional staff (Schneijderberg and Merkator 1 The principle of actorhood taps into the important assumption at the basis of the modern society, namely the ability of the individual to act autonomously and play a central constitutive role in the wider public life. This presupposes the centrality of the individual as an autonomous entity of high relevance to the collective good (Frank et al 1995). 2013; Baltaru and Soysal 2017). The author argues that in order to fully understand universities' organisational responses to the external demands, one must consider the broader cultural forces that shape universities as formal organisations.…”
Section: Individual Empowerment and Universities' Pursuit Of Inclusionmentioning
confidence: 99%
See 1 more Smart Citation